How is communication effective in control of inflation in Merauke regency? - Yulianti, Ni Luh Putu Nita; Ismail, Ismail; Kadir, Syahruddin (Nur Science Institute, 2025)
This article examines the importance of effective communication in controlling inflation in Merauke Regency. Merauke, known for its geographical and economic challenges, requires a strong communication strategy to control inflation, which is often influenced by external and internal factors. Through a literature study of secondary data analysis, this article explores how effective communication between the government, the community, and the private sector can play a role in maintaining price stability and supporting sustainable economic development in an inflation control program. By adopting the right communication strategies, such as the use of mass media, direct socialization, and the involvement of community leaders, the government can increase public awareness and participation. Although there are challenges in communication infrastructure and varying literacy levels, increasing investment in infrastructure and community training can help overcome these challenges. The strategic recommendations provided in this study are hoped to help the government and other stakeholders design and implement effective communication strategies to control inflation in the Merauke Regency.